Islam dalam Pusaran Konflik: Syiah dan Sunni Era Dinasti Safawi - Aji, Aji Cahyono (Journal of Integrative International Relations, 2022)
Discussing about Islam really takes time with a long or unlimited scale when viewed from a comprehensive multi-segmentation. Even some non-Western scholars are trying their luck researching Islam. It is generally known that Islam under the Prophet Muhammad was full of peace. After his death, peace between fellow Muslims seems not to be a shared dreams, until now sectarian conflicts often occur, namely Shia and Sunni Islam. In this study, this time the author tries to write about the topic of Islam in the Vortex of Conflict between Shia and Sunni, which is focused on the boundaries of the Safavid era. In this case, this research uses a historical approach and research methods using literature studies. The results of this study found that first, before the formation of the Safavid dynasty, Islam was hit by sectarian conflicts between Shia and Sunnis after the death of the Prophet Muhammad, because for general reasons they were still debating who should replace Rasulullah SAW as the leader of Muslims. Second, the establishment of the Safavid dynasty in the era of King Ismail I caused the Sunni sect and all its activities to be converted to Shia sects in the Persian region either in fiqh or theology..